µUAS: New tools for monitoring coastal resilience - Graves, Scott M (Regions, 2017)
Keywords: dept.egm; ⛔ No DOI found

Data and policy scale mismatch in coastal systems : The potential of μUAS as new tools for monitoring coastal resilience - Graves, Scott M. (Towards Coastal Resilience and Sustainability, 2018)
An important challenge in monitoring, planning and evaluating coastal saltmarsh resources in the face of predicted sea level rise (SLR) using numerical
Keywords: 3D modeling; Antennas; Coastal systems; Flight planning; Model results; Numerical models; Remotely sensed data; Scale mismatches; Sea level; Sea level rise; Structure from motion; Unmanned aerial systems; Unmanned aerial vehicles (UAV); Wetlands; dept.egm

Towards Coastal Resilience and Sustainability - Heidkamp, C. Patrick; Morrissey, John; Graves, Scott M. (Routledge, 2019)
"Coastal zones represent a frontline in the battle for sustainability, as coastal communities face unprecedented economic challenges. Coastal ecosystems are subject to overuse, loss of resilience and increased vulnerability. This book aims to interrogate the multi-scalar complexities in creating a more sustainable coastal zone. Sustainability transitions are geographical processes, which happen in situated, particular places. However, much contemporary discussion of transition is either aspatial or based on implicit assumptions about spatial homogeneity. This book addresses these limitations through an examination of socio-technological transitions with an explicitly spatial focus in the context of the coastal zone. The book begins by focusing on theoretical understandings of transition processes specific to the coastal zone and includes detailed empirical case studies. The second half of the book appraises governance initiatives in coastal zones and their efficacy. The authors conclude with an implicit theme of social and environmental justice in coastal sustainability transitions. Research will be of interest to practitioners, academics and decision-makers active in the sphere of coastal sustainability. The multi-disciplinary nature encourages accessibility for individuals working in the fields of Economic Geography, Regional Development, Public Policy and Planning, Environmental Studies, Social Geography and Sociology" – Provided by publisher's website.
Keywords: Coastal zone management; Economic aspects; Economic aspects; Sustainable development; dept.egm; faculty_collection

A mentoring model for interactive online learning in support of a technology innovation challenge grant - Graves, Scott M; Abbitt, Jason; Klett, Mitchell; Wang, Changhua (Journal of Computing in Teacher Education, 2009)
Citation Key Alias: lens.org/050-172-410-980-553 tex.type: [object Object]
Keywords: dept.egm; ⚠️ Invalid DOI

Examining historical land management and current urban forest health - Massa, Amanda; Zavar, Elyse; Lavy, Brendan L.; Graves, Scott M. (Northeastern Geographer, 2018)
Urban forests can serve as valuable oases for birds and other wildlife in densely-populated urban and suburban areas with proper management. This study analyzes forest health and habitat availability of a publically-owned urban forest in West Haven, Connecticut. During the first half of the twentieth-century, this urban forest was privately-owned and primarily managed as an orchard and meadow for grazing horses. By the mid-twentieth-century, farming dwindled on the land and vegetation overtook the property. Today, this closed-canopy forest, with access to both freshwater streams and marshlands, provides habitat to a variety of native and invasive plant and animal species. By identifying the forest species and characteristics of the six hectare Cove River Historic Site (CRHS) urban forest, this study serves as the first forest inventory and provides a baseline dataset to help manage an ecologically important urban forest. Additionally, we identified bird habitat opportunities and bird species at the property. This study considers both the historic land management practices of this site in tandem with present-day forest health and animal activity to understand how this fragmented forest contributes to local biodiversity. The results indicate that this property, located within the urban environment of the central Connecticut coastline, offers varied habitats and food sources for many resident and migratory bird species, as well as wildlife including foxes.
Keywords: BIRD habitats; FOREST health; LAND management; MIGRATORY birds; URBAN forestry; bird habitat; conservation; dept.egm; invasive species; land management; peer-reviewed; urban forestry; ⛔ No DOI found